Quality improvement of rubber seed meal diet for Nile tilapia with amino acid supplemetation - Yusuf, Didi Humaedi; Suprayudi, Muhammad Agus; Jusadi, Dedi (Indonesian Society of Scientific Aquaculture (ISSA), 2016)
ABSTRACT This experiment was conducted to improve the quality of rubber seed meal fermented using sheep rumen liquor based diet (RSMF) with amino acid supplementation for Nile tilapia Oreochromis niloticus. This experiment consisted of five treatments with three replications. The treatments were 0% protein from RSMF as control; 50% RSMF; 50% RSMF with lysine; 75% RSMF and 75% RSMF with lysine. Tilapia with an initial body weight of 6.29±0.12 g were reared for 40 days and the fish were fed three times daily at satiation level (8.00 am, 12.00 pm and 16.00 pm). The data were statistically analysed by using one-way analysis of variance (ANOVA) using software SPSS version 16.0 at 95% (p<0.05) confidence interval and Tukey test for the post hoc test. The results showed that the addition of lysine in the 75% RSMF diets could increased final weight, but did not significantly different to protein efficiency ratio (PER), decreased feed convertion ratio (FCR) and biochemical body composition. The data indicated that quality of 75% RSMF could improved after lysine supplementation, but still lower than using 50% RSMF and soybean meal as protein source. Keywords: amino acid supplementation, Oreochromis niloticus, rubber seed meal ABSTRAK Penelitian ini dilakukan untuk meningkatkan kualitas pakan dengan tepung bungkil biji karet yang difermentasi dengan cairan rumen domba (TBBKF) melalui suplementasi asam amino untuk ikan nila Oreochromis niloticus. Penelitian ini terdiri atas lima perlakuan dengan tiga ulangan. Perlakuan terdiri atas 0% protein dari TBBKF sebagai kontrol; 50% TBBKF; 50% TBBKF + Lisin; 75% TBBKF dan 75% TBBKF + lisin. Ikan nila dengan bobot awal 6,29±0,12 g dipelihara selama 40 hari dan pemberian pakan dilakukan tiga kali sehari hingga sekenyangnya (08.00, 12.00 dan 16.00 WIB). Data dianalisis menggunakan analisis sidik ragam (ANOVA) dengan menggunakan software SPSS 16.0 dan diuji lanjut menggunakan uji Tukey. Hasil penelitian menunjukkan bahwa penambahan lisin pada pakan 75% TBBKF meningkatkan bobot tubuh ikan akhir, tetapi tidak berpengaruh signifikan terhadap rasio efisiensi protein (PER), rasio konversi pakan (FCR) dan komposisi biokimia tubuh ikan nila. Hasil penelitian ini menunjukkan bahwa kualitas protein 75% TBBKF meningkat setelah suplementasi lisin, tetapi masih lebih rendah dibandingkan dengan penggunaan 50% TBBKF dan tepung kedelai sebagai sumber protein. Kata kunci: suplementasi asam amino, Oreochromis niloticus, tepung biji karet